"Urban sprawl" - Ravbar, Marjan (Geografski vestnik, 2005)
This paper attempts to clarify some of the most frequently used contemporary concepts and critical considerations of the thematic complex that in a unified system combines urban growth and geographical changes in the form of land use in urban areas of influence. In the discussion we focus on the effects of spatial expansion that bring with them new forms of urbanization. The dispersion of the urban lifestyle and its related economic activities are of key importance in understanding modern forms of settlement.
Keywords: urbana geografija; geografija naselij; mesta; obmestja; podeželje; rural area; urbanizacija; suburbanizacija; Slovenia; Slovenija